Changes in the content of carotenoids and flavonoids in medicinal raw material of Digitalis purpurea, Polemonium caeruleum, and Aerva lanata, cultivated in vitro under the chronic action of ionizing radiation - S. V. Litvinov; L. G. Lioshyna; O. V. Bulko; K. V. Lystvan; S. A. Pchelovska (Ядерна фізика та енергетика)
Chronic low-dose γ-irradiation of Digitalis purpurea and Aerva lanata plants in vitro have led to an increase in the content of carotenoids and flavonoids in the leaves at the beginning of the post-radiation period. In the following, the content of pigments and flavonoids decreased in comparison to the control samples. For Polemonium caeruleum such changes had been not observed. The qualitative composition of the secondary metabolites has not been changed, but the ratio of the individual components of the extract varied within a small range. Ri-transformants of Digitalis purpurea have been shown smaller changes in response to irradiation. We assume that the observed effects are the manifestation of the adaptive response of plants to oxidative stress caused by chronic low-dose irradiation.